Effectiveness of the Digital Population Identity (IKD) Program at the Population and Civil Registration Office of Bogor Regency - Therasari, Anita; Salbiah, Euis; Apriliyani, Neng Virly (Public Policy Journal, 2025)
The implementation of the Digital Population Identity (IKD) is one of the government’s efforts to digitize public services, particularly in the area of civil registration. This study aims to evaluate the effectiveness of the IKD program conducted by the Department of Population and Civil Registration (Disdukcapil) of Bogor Regency. The research uses a descriptive quantitative approach to gain a statistical picture of public perceptions of the program. Data were collected from 100 respondents through a structured questionnaire, supported by interviews with key officers at Disdukcapil. The effectiveness of the IKD program was measured using five dimensions proposed by Sutrisno (2010): program understanding, target accuracy, timeliness, goal achievement, and actual change. The results of this study indicate that the IKD program in Bogor Regency is considered effective, with an overall average score of 3.83, categorized as "good." The highest score was achieved in the program understanding dimension (3.97), which shows that most of the community already understands how to access and use IKD services. However, the lowest score was found in the timeliness dimension (3.71), indicating that technical issues such as poor internet access, limited digital literacy, and application errors are still obstacles in the field. Interviews also revealed that socialization efforts must be strengthened, and the system interface must be simplified to accommodate citizens with low digital skills. This study contributes by filling the research gap on the regional implementation of digital identity services from a quantitative perspective. While previous studies often focused on national-level policies or technological design, this research provides empirical evidence of how the IKD program performs in practice at the local level. The findings suggest that strengthening public understanding is key to increasing program effectiveness. Policymakers are encouraged to improve education, infrastructure, and application usability to ensure inclusive and sustainable digital public services.